Critical Pre-Design Factors for Constructive Durability: Anglican Chapel of Chañaral, in Chile [Factores Críticos de Pre-Diseño Para la Durabilidad Constructiva. Capilla Anglicana de Chañaral, Chile] - Alvarez-Gutierrez, P; Vidal-Rojas, R (Universidade do Vale do Rio dos Sinos, 2021)
Knowing the causes of the durability of a 143-year-old wooden building, in the face of adverse atmospheric agents, allows us to understand the role that these causes play in architectural design. This is the case of the Anglican chapel of Chañaral, in Chile. The hypothesis is proposed that the critical pre-design conditions and decisions determined the design decisions and allowed the construction of a stable, durable and sustainable building, given the conditions of the place, before the design itself and in the absence of a conservation program. . An inductive logic method was applied which, after observing the building, its context and the inductive derivation, allowed via experimentation to conclude that the pre-design conditions were: accurate and adequate reading of the structure of the place of intervention; the selection of a coherent set of mitigation actions to reduce the adverse factors of the site and three key pre-design decisions: siting and orientation; material and construction system; resistance to weathering. © 2021, Universidade do Vale do Rio dos Sinos. All rights reserved.